2021
DOI: 10.22146/jaci.v7i2.3520
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Peripheral Arterial Disease in type 2 Diabets Mellitus in Yogyakarta, Indonesia

Abstract: Aim: Diabetes mellitus increases the risk of peripheral artery disease (PAD) 2 times. PAD is diagnosed by ABI (Ankle Brachial Index). PAD increases mortality and morbidity of patient with Diabetes Mellitus (DM) Type 2. This study aims to determine the prevalence and risk factors of PAD in the population of type 2 diabetes mellitus (DM) in Yogyakarta, Indonesia.   Methods: This study was a community-based descriptive and analytic observational study that examines the prevalence and risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Peripheral arterial disease (PAD), a well-known macrovascular complication of diabetes mellitus, affects about 236 million adults worldwide and is more prevalent in high-income than in low-income countries [1]. A study in Indonesia, conducted by Ismail et al, reported that PAD prevalence in type 2 diabetes mellitus (T2DM) patients is 16% [2]. Atherosclerosis is the most common cause of PAD.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral arterial disease (PAD), a well-known macrovascular complication of diabetes mellitus, affects about 236 million adults worldwide and is more prevalent in high-income than in low-income countries [1]. A study in Indonesia, conducted by Ismail et al, reported that PAD prevalence in type 2 diabetes mellitus (T2DM) patients is 16% [2]. Atherosclerosis is the most common cause of PAD.…”
Section: Introductionmentioning
confidence: 99%